2020
DOI: 10.1002/jms.4613
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of space charge effects and ion trapping capacity on direct introduction ultra‐high‐resolution mass spectrometry workflows for metabolomics

Abstract: Ultra-high-resolution mass spectrometry, in the absence of chromatography, is finding its place for direct analyses of highly complex mixtures, such as those encountered during untargeted metabolomics screening. Advances, however, have been tempered by difficulties such as uneven signal suppression experienced during electrospray ionization. Moreover, ultra-high-resolution mass spectrometers that use Orbitrap and ICR analyzers both suffer from limited ion trapping capacities, owing principally to space-charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Increasing magnetic field strength will increase mass resolution, dynamic range, and peak noncoalescence. , Increasing the time-domain acquisition period will also increase resolution; however if sample signal magnitude is low (i.e., sample ions are very low in abundance), instrument noise can also erroneously be assigned . Increasing ion accumulation times can increase sensitivity; however high ion densities in the ICR cell can produce space charge effects that coalesce peaks or alter ion frequencies, adversely affecting both formula assignment and mass accuracy. ,,, The limited ion capacity during FTICR MS measurement also means that intensity and m / z distributions are sensitive to instrumental parameters. Molecular weight distributions are better determined in low resolution MS systems like linear ion trap and time-of-flight that also capture lower molecular weights (<200 m / z ) efficiently. , Thresholds for S/N will also strongly affect peak detection and reproducibility.…”
Section: Analysis and Interpretation Of Soil Organic Matter Using Fti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing magnetic field strength will increase mass resolution, dynamic range, and peak noncoalescence. , Increasing the time-domain acquisition period will also increase resolution; however if sample signal magnitude is low (i.e., sample ions are very low in abundance), instrument noise can also erroneously be assigned . Increasing ion accumulation times can increase sensitivity; however high ion densities in the ICR cell can produce space charge effects that coalesce peaks or alter ion frequencies, adversely affecting both formula assignment and mass accuracy. ,,, The limited ion capacity during FTICR MS measurement also means that intensity and m / z distributions are sensitive to instrumental parameters. Molecular weight distributions are better determined in low resolution MS systems like linear ion trap and time-of-flight that also capture lower molecular weights (<200 m / z ) efficiently. , Thresholds for S/N will also strongly affect peak detection and reproducibility.…”
Section: Analysis and Interpretation Of Soil Organic Matter Using Fti...mentioning
confidence: 99%
“…20 Increasing ion accumulation times can increase sensitivity; however high ion densities in the ICR cell can produce space charge effects that coalesce peaks or alter ion frequencies, adversely affecting both formula assignment and mass accuracy. 20,125,148,149 The limited ion capacity during FTICR MS measurement also means that intensity and m/z distributions are sensitive to instrumental parameters. Molecular weight distributions are better determined in low resolution MS systems like linear ion trap and time-of-flight that also capture lower molecular weights (<200 m/z) efficiently.…”
Section: ■ Analysis and Interpretation Of Soil Organic Matter Using F...mentioning
confidence: 99%
“…We believe that the differences between resolution and mass accuracy for the assignments shown in Figure 5 can be attributed to space-charge phenomena, which are closely related to the total ions and the number of species per nominal mass. 54 In a recent contribution, Hohenester et al 55 reported several analytical considerations for space-charge phenomena in FT-ICR using the Bruker SolariX equipped with the Paracell, the same instrument used in this work. The authors found that raising the number of ions within the cell due to increased accumulation times or use of concentrated samples affected the spectral mass accuracy.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…13 DI-MS with segment scan has also been used for metabolome analysis with improved coverage compared to full scan in various metabolomics applications. 9,11,12 In addition, segment scan has been shown to increase the accuracy of isotopic ion abundance measurement in a targeted metabolic flux analysis (e.g., by reducing the space-charge effect) with separate scans of two segments, instead of one full scan, in LC−Orbitrap−MS. 14 However, to our knowledge, there is no report of detailed study of segment scan mass spectral acquisition for increasing the metabolomic coverage in an LC−MS-based metabolome analysis.…”
Section: ■ Introductionmentioning
confidence: 99%